2013
DOI: 10.1111/jen.12090
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of aphids by augmentative release of larvae of flightless Harmonia axyridis

Abstract: The release of the larvae of flightless ladybird beetles could extend the duration of effective control because of the longer presence of adult stages, and the per individual production cost for juvenile stages is lower than that for adult stages. A preliminary release experiment was conducted to assess the effectiveness in controlling two aphid species, Aphis gossypii and Aulacorthum solani, using second instars of a flightless strain of Harmonia axyridis. The number of A. gossypii was suppressed in greenhous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…There is a growing body of evidence that limiting the flight ability of ladybirds prolongs their residence time on aphid‐infested host plants and can thus enhance biological control efficacy compared to conspecific winged ladybirds (Ignoffo et al., ; Ferran et al., ; Tourniaire et al., ; Weissenberger et al., ; Seko et al., , ; Iguchi et al., ). Therefore, the trait targeted for breeding selection was reduced flight ability.…”
Section: Example Of a Target Species: The Two‐spot Ladybird Beetlementioning
confidence: 99%
“…There is a growing body of evidence that limiting the flight ability of ladybirds prolongs their residence time on aphid‐infested host plants and can thus enhance biological control efficacy compared to conspecific winged ladybirds (Ignoffo et al., ; Ferran et al., ; Tourniaire et al., ; Weissenberger et al., ; Seko et al., , ; Iguchi et al., ). Therefore, the trait targeted for breeding selection was reduced flight ability.…”
Section: Example Of a Target Species: The Two‐spot Ladybird Beetlementioning
confidence: 99%
“…However, it has been demonstrated in several taxonomic groups that behavioral differences among individuals have considerable ecological consequences (Sih et al, 2004(Sih et al, , 2012Réale et al, 2007;Araújo et al, 2011;Bolnick et al, 2011). Recently, some studies have demonstrated that native biological control agents can be improved by exploiting intraspecific behavioral differences in various traits related to their efficiency (Lommen et al, 2008(Lommen et al, , 2013Tabone et al, 2010;Nakayama et al, 2013: Seko et al, 2014Dumont et al, 2016Dumont et al, , 2017a. Therefore, some authors (Hoy, 1986;Rosenheim and Hoy, 1988;Hopper et al, 1993;Nachappa et al, 2010Nachappa et al, , 2011Lommen et al, 2013Lommen et al, , 2017Dumont et al, 2016Dumont et al, , 2017aKruitwagen et al, 2018) suggested that genetic improvement of biocontrol agents could rely on intraspecific behavioral differences.…”
Section: Toward Artificial Selectionmentioning
confidence: 99%
“…In another study, 2nd instar larvae or adults of a flightless strain of H. axyridis were tested against A. solani on cultivated eggplants Solanum melongena (L.) [ 57 ]. A total of 600 larvae or 120 adults were released three times in the test plots, respectively; no predators were released in the control plots.…”
Section: Factors Potentially Affecting Ladybird Success In Greenhomentioning
confidence: 99%
“…Thus, A. solani population density was reduced by 66.7% in both test plots, when compared against the control plot ( Table 1 ). Approximately 35 days after the third release of larvae and adults, A. solani density was reduced by 70% and 60% in the larval release and adult release plots, respectively, compared against the control plot [ 57 ]. Since the larval stage does not last more than 14 days at ambient conditions, much of the predation in the larval release plot beyond 21 days after the third release was certainly due to newly metamorphosed adults.…”
Section: Factors Potentially Affecting Ladybird Success In Greenhomentioning
confidence: 99%